The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jopr.12393
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Molar Crowns Fabricated with Monolithic All‐Ceramic CAD/CAM Materials Cemented on Titanium Abutments: An In Vitro Study

Abstract: There was no accordance between the F-initial and F-max values of the LD, RNC, and FEL after chewing simulation with thermocycling resembling 5 years of clinical functional use. LD had the highest fracture resistance during the fracture test. RNC had low fracture resistance; however, it had considerably high fracture resistance during the fracture test. FEL had considerably low fracture resistance values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
1
31
0
3
Order By: Relevance
“…The other 16 specimens of each material were subjected to aging followed by either the fracture load test of the 8 polished specimens or retention test of the 8 unpolished specimens as described above. For the aging simulation, the crowns were first placed in a chewing simulator (CS-4.8, SD Mechatronik, Feldkirchen, Germany) and subjected to 1.2 Mio cycles [20,23,24,26,27] with a frequency of 1.5Hz (maximal capacity of the chewing simulator) and a force of 49N to initiate subcritical crack growth [20,[26][27][28]. Steel balls with a diameter of 4.5mm served as antagonists.…”
Section: Loading and Retention Capacity Of The Restorative Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 16 specimens of each material were subjected to aging followed by either the fracture load test of the 8 polished specimens or retention test of the 8 unpolished specimens as described above. For the aging simulation, the crowns were first placed in a chewing simulator (CS-4.8, SD Mechatronik, Feldkirchen, Germany) and subjected to 1.2 Mio cycles [20,23,24,26,27] with a frequency of 1.5Hz (maximal capacity of the chewing simulator) and a force of 49N to initiate subcritical crack growth [20,[26][27][28]. Steel balls with a diameter of 4.5mm served as antagonists.…”
Section: Loading and Retention Capacity Of The Restorative Systemmentioning
confidence: 99%
“…The effect of aging in the intraoral environment is simulated by subjecting the specimens to procedures such as dynamic loading and/or thermocyclic aging [12,18,[19][20][21]23,24]. However, in most studies only fracture load or retentive force values of the whole system are measured and the components by themselves are not properly characterized, which leads to a lack of data to interpret the obtained results.…”
Section: Introductionmentioning
confidence: 99%
“…The IPS e.max CAD's characteristics of high strength, the ability to be milled to full-contour esthetics, and dual placement (bond or cement) are useful in creating in-office implant restorations and thin veneers, or in any other situation in which strength and esthetics should be carefully balanced [5]. From in vitro studies, there is strong evidence that monolithic restorations, in contrast to bi-layered restorations, show fracture strength and fatigue resistance suitable for use in posterior areas, both in single implant-supported and 3-unit fixed prostheses [107][108][109][110][111]. In vitro fully anatomical e.max CAD crowns have been shown to exhibit fracture resistance that is suitable for posterior, monolithic restorations and to be more resistant to fatigue in cyclic loading than veneered zirconia, which is more prone to chipping [112,113].…”
Section: Lithium Disilicate Glassmentioning
confidence: 99%
“…Several studies have analyzed the influence of the cement type on fracture load values of tooth-supported restorations and showed that feldspathic ceramic should be bonded adhesively to the abutment tooth to enhance strength and longevity (Attia, Abdelaziz, Freitag, & Kern, 2006;Borges et al, 2009;Groten & Probster, 1997). Implant-supported crowns fabricated from feldspathic ceramics cemented with self-adhesive resin cement have demonstrated values between 220 ± 50 N for initial fracture load and 1,130 ± 220 N for maximum fracture load (Dogan et al, 2017). In the meantime, several in vitro studies investigated the influence of crown material and cement on the fracture load of zirconia implant-supported crowns (Kohal, Kilian, Stampf, & Spies, 2015;Rohr, Coldea, Zitzmann, & Fischer, 2015).…”
Section: Introductionmentioning
confidence: 99%